Role of Procalcitonin in Intracerebral Hemorrhage Stroke with COVID-19 - Ita Muharram Sari; Iswandi Erwin; Fiizhda Baqarizky; Puspa Oktaviani; Sardiana Salam; Anna Mardiana Ritonga (Universitas Airlangga, 2022)
Introduction: As COVID-19 has rapidly spread worldwide, it is an urgent health problem. Some evidence suggests that SARS-CoV-2 also affects the central nervous system. Stroke is the most common disease of the central nervous system. In contrast to ischemic stroke, which can occur due to the hypercoagulation effect of COVID-19, the study of Intracerebral Hemorrhage (ICH) associated with COVID-19 is still unclear. Objective: This paper investigated the characteristics of an inflammatory biomarker and compared the outcomes of ICH patients with COVID-19 and ICH patients without COVID-19. Methods: We conducted a retrospective, observational analysis case-control of patients (n = 42) admitted with ICH with positive COVID-19 and ICH with negative COVID-19 at the National Brain Center Hospital Prof.Dr.dr. Mahar Mardjono from March 2020 to August 2021. We took blood samples and COVID-19 swab PCR on the first day of admission, and GOS was measured when the patients were discharged. Results: There were 21 ICH patients with positive COVID-19 who had a significantly procalcitonin (p < 0.05) compared to control patients. From Spearman’s correlational analysis, there is a significant value between early procalcitonin and the Barthel Index (rs = -0,374, p < 0.05), early CRP and GOS (rs =- 0.329, p < 0.05), which indicates weak-inverse correlation, and between early PCT and GOS (rs = -0.438, p < 0.05) which indicates moderate-inverse correlation. Conclusion: The level of procalcitonin was increased in ICH patients with COVID-19. Maybe PCT could be a predictor of outcome in ICH patients with COVID-19.